Zum Stand der Forschungen auf dem Gebiet der Sumerologie - Neumann, Hans
Besprechungsartikel von Sjöberg, Ǻ.W. (Ed.), The Sumerian Dictionary of the University Museum of the University of Pennsylvania. Vol. 2: В (1984) 47:1605.